Zoos - Lee, K. author. aut Link
VIII, 174 p.
Keywords: In this book, Keekok Lee asks the question, 'what is an animal, and how does our treatment of it within captivity affect its status as a being ?' This ontological treatment marks the first such approach in looking at animals in captivity. Engaging with the moral questions of zoo-keeping (is it morally justified to keep a wild animal in captivity?) as well as the ontological (what is it that we conserve in zoos after all? A wild animal or its shadow?), Lee develops her own original hypothesis, centred around the concept of 'immuration' - defining this in contrast to domestication - and thereby provides a unique addition to the growing body of work on animal ethics.